PENELITIAN TENTANG MANFAAT LAPORAN ARUS KAS - Arief Suadi (Journal of Indonesian Economy and Business (JIEB), 1998)
Effective 1994, the Indonesian Institute of Accountants made it mandatory for companies in Indonesia to prepare cashflow statement instead of fund flow statement. The reasons stated by the Institute for the change are: (I) historical cash flow is important in predicting the amount, timing, and certainty of future cashflow, and (2) to check the accuracy of future cashflow estimate.For stockholders, the cash inflow consists of cash dividend (hereafter dividend) and sales proceed of the investment. The estimation of proceed from investment sales is difficult because it is dependent on the economy and the expectation of security market. On the other hand, the estimate of total dividend payment is relatively easier to make. By law, a company can pay dividend only if it has profit. For the obvious reason, it can pay dividend, only if it has money. Using, the rules, a regression model is developed The dependent variable is total dividend (DIV) for year (n+1), while the dependent variables are cash provided by operation (AKO) in year n, and ending cash balance (KAT) for year n. The independent variables are components of the cash flow statement.Regression analysis showed that the independent variables explain 56$6 of total dividend payment and that the two independent variables, AKO and KAT, are significant withp-value of 0,0001 and 0,0236, respectively. The study rejected the null hypothesis and concluded that cashflow report is related to the dividend payment in the following year  and therefore cash flow statement is useful for stockholders.